A review of the role of nurses and technicians in ST-elevation myocardial infarction (STEMI) - Zughaft, David; Harnek, Jan (EuroIntervention, 2014)
The role of nurses and technicians in the treatment of ST-elevation myocardial infarction (STEMI) by primary percutaneous coronary intervention (PPCI) is vital for the success of the multidisciplinary Heart Team. Several editorials have emphasised the importance of a holistic treatment which links each step of care to the next, a chain that is essential for quality and efficacy in the management of STEMI patients. In pre-hospital acute coronary care, the first medical contact is most commonly a nurse and/or a paramedic. The time from symptom onset to reperfusion is crucial for the long-term outcome. On arrival at the hospital, it is important for the nurse or paramedic to share an overview of what has been done to the patient so far, in a structured and evidence-based way, with the receiving nurse and physician. During PPCI, the role of nurses and technicians includes puncture site assessment, administration of pharmaceuticals and the ability to anticipate and prevent complications. In patients with cardiogenic shock and cardiac arrest, advanced knowledge of haemodynamic support systems is required. In the future, this knowledge must be extended from a limited number of individuals in a small number of centres to a standard of care which is available for all citizens throughout Europe. This review demonstrates the necessity for a multidisciplinary team approach where every person plays an equal, important role in every element of PPCI. The future role of nurses and technicians is intriguing and demands education and experience from an advanced medical and nursing point of view, where the multidisciplinary Heart Team and the knowledge of the different key players are vital.